Pengaruh Pemberian Kompres Hangat Terhadap Penurunan Nyeri Dismenore Pada Siswi Kelas XI SMK Muhammadiyah Watukelir Sukoharjo (The Influence Of Warm Compress Decrease In Dismenorhea Eleventh Grade Students Of SMK Muhammadiyah Watukelir Sukoharjo) - Rima Maratun Nida; Defie Septiana Sari (Jurnal Kebidanan dan Kesehatan Tradisional, 2016)
Abstract: Warm Compress,Disminorhea. Puberty is a stage of development characterized by the maturity of the sexual organs and achieving the capability to reproduce, in which one of the characteristics of the signs of puberty a woman is the first occurrence of menstruation (menarche). When it happened the first menstruation (menarche) and the next menstruation, a woman will experience abdominal pain (disminorea), when the abdominal pain disorder (disminorea) are not adequately addressed; it can be debilitating to the decrease in performance. Disminorea that occurs continuously in each period, can be one of the symptoms of endometriosis on the reproductive system. One way that can be done to overcome disminorea by performing a warm compress, which is done to meet the needs of a sense of comfort, reduce or relieve pain, reduce or prevent muscle spasms and provide a sense of warmth in the abdomen (stomach). Warm compresses can be done by attaching a rubber bag filled with warm water or a towel that has been soaked in warm water, to the painful body part. The purpose of this study was to determine the effect of a warm compress against dysmenorrhea pain reduction in eleventh student at SMK Muhammadiyah Watukelir Sukoharjo. This type of research is quasi experiment with one group pretest-posttest design with purposive sampling technique sampling number of 30 respondents. Analysis of the data using the Wilcoxon signed-rank test. The results of this study indicated the presence of a warm compress against dysmenorrhea pain reduction in eleventh student at SMK Muhammadiyah Watukelir, with a p-value of 0.000 (p <0.05).